Increased serum levels of IL-40 are associated with IgA and NETosis biomarkers in Covid-19 patients: IL-40 and infectious diseases - Umit Bagriacik; Resul Karakus; Melek Yaman; Nihan Oruklu; Milat Araz; Zafer Kalayci; Hasan Selcuk Ozger; Yesim Yildiz; Esin Senol (PLoS ONE, 2025)
Interleukin 40 (IL-40) is a novel cytokine that has been associated with B lymphocytes, particularly IgA-secreting cells in gut mucosa. Considering mucosal association of IL-40, we aimed to determine serum IL-40 levels in patients with Covid-19. We compared IL-40 concentrations in healthy people to both patients with mild symptoms of SARS-CoV-2 infection and pneumonia. IL-40 was measured by ELISA. Serum IgA levels were tested by nephelometry. For the first time, we demonstrated that SARS-CoV-2 infection increased serum IL-40 levels significantly. The elevation of IL-40 in serum was related to severity of the infection. Therefore, IL-40 concentrations were quite higher in patients with symptoms of pneumonia. Our findings indicated that IgA and NETosis biomarkers were related with IL-40 increase. Based on these findings, we speculated that IL-40 would be associated with immune activities in the mucosa of the lungs of SARS-CoV-2-infected patients. This association may be linked to a mechanism that has a control on IgA and NETosis.